Prognostic Value of KI6 Biomarker to Predict Short Term Prognosis of Low Grade Cervical Intraepithelial Neoplasia in Human Papilloma Virus Negative and Positive Patients - Leila Mousavi Seresht; Noorieh Sharifi; Mona Najafi; Helena Azimi; Nooshin Babapour; Zohreh Yousefi; Nazanin Beheshtian; Yasaman Nikooiyan (Middle East Journal of Cancer, 2019)
Background: Screening of cervical cancer is the most common gynecologic cancer in developing countries. Despite being preventable, but we have still some problems in the screening of this cancer. Recently, many studies have been done on immunohistochemistry to improve screening of cervical intraepithelial neoplasia (CIN) as precancerous lesion. But, majority of the studies are based on cytological samples.The objective of this study was to analyze the correlation KI-67 biomarker and HPV infection in predict short time prognosis in CIN as an alternative or auxiliary method to current screening method in a different geographic population.Methods: This descriptive cohort prospective study included 40 patients with diagnosis of CIN based on cervical punch biopsy samples after colposcopy examination. They were referred to the department of gynecology and oncology of an academic hospital, Mashhad University of   2016 to 2017. All samples were investigated for HR- HPV DNA with Cobas test and immunostaining for KI-67 biomarker. Finally, after one year follow up, prognosis for all patients was evaluated. Data were analyzed by SPSS software program version 23.0 and Mann-Whitney U test and Fisher's exact test. P-value< 0.05 was considered significant.Results: significant difference was found between HR-HPV positive and negative tests in KI-67 expression (P<0.001), but no significant difference was observed in reactivity level (P=0.5), also no significant difference was found in KI-67 expression in metaplastic and non-metaplastic epithelium (P=0.88),.Conclusion:  KI-67 biomarker is recommended as complementary screening tests not alternative for differentiating in high risks patients with CIN1. The patients with low KI-67 / HR-HPV positive could be offer for a less aggressive follow-up protocol.